The Impact of Work-Based Learning on Graduates Job Performance: Insights from School-in-Factory (SiF) Project - schlattmann, siriphorn; Chaiyong, Patcharee; Moonpa, Niwat (Journal of Technical Education and Training, 2024)
The School-in-Factory (SiF) is a pilot project for implementing dual technical and vocational education and training in Thailand by using a Work-based Learning approach with the combination of learning and working in the real process of work through the collaboration between the private company and educational institute. This study aims to evaluate the output and outcome of the SiF project by analyzing the program completion rate and the impact of the SiF project on the graduates’ job performance in the labour market. The study employed both quantitative and qualitative approaches. The quantitative data is collected from official project records. The qualitative data is collected by using an open-ended. It is found that 85% of the learners from the year 2017-2020 successfully completed the SiF program (100 out of 117 learners). The impact of the SiF program has mostly contributed to the development of subject-oriented competence, that is technical knowledge and skills of the learners. The graduates reported that the SiF program has a positive impact on their performance where knowledge of the work process, ability to adapt to the workplace, and valuable work experience gained during training are the most valued impact. Moreover, from the perspective of the employers, the employees who graduated from the SiF program have shown their competencies in technical proficiency and job professional behaviour, constructive communication and expression, teamwork, job- related problem-solving skills. The results of the study stressed the importance of work-based learning where training at the company and learning at the classroom are combined, like the SiF program, to support learner competency development. The SiF program has shown a strong collaboration with the private company partner in implementing work-based learning in Thailand. Further studies should be conducted to find out the financial benefits of the project.